A contest of ideas : capital, politics, and labor - Lichtenstein, Nelson (Working class in American history., 2013)
For more than 30 years the author of this work has deployed his scholarship, on labour, politics, and social thought, to chart the history and prospects of a progressive America. This work collects and updates many of the author's most provocative and controversial essays and reviews.